A qualitative study of the implementation and organization of the national Greenlandic addiction treatment service - Flyger, Julie; Larsen, Christina Viskum Lytken; Jensen, Else; Niclasen, Birgit; Nielsen, Anette Søgaard (Frontiers in Health Services, 2024)
Background Alcohol and cannabis use constitutes the major public health problems in Greenland. Thus, it is important to assess if Allorfik, a new national outpatient addiction treatment service introduced in 2016, was implemented successfully and how it is perceived. Allorfik introduced local treatment centers offering a treatment methodology (motivational interviewing and cognitive therapy) new to addiction treatment in Greenland with limited evidence from Indigenous populations such as the Greenlandic. The present study investigates the implementation of Allorfik from the perspective of those engaged in the process and the field. Methods Data consisted of transcribed interviews with 23 individuals from both Allorfik and organizations collaborating with or supposed to collaborate with Allorfik. The theme of the interviews was their perspectives on the implementation process, enablers, and obstacles in the process and how Allorfik was performing at the time of the interview. The interview guide was informed by implementation theory. The transcribed material was analyzed using a general inductive approach. Results The analysis resulted in three overall and interconnected themes, namely, implementation, collaborations, and challenges. The implementation was overall considered a success by the interviewees as all components were implemented as planned with a few adaptions, e.g., a treatment guideline update. The collaborations are considered challenging but important to all interviewees. Collaborations seem to rely on personal commitment as opposed to well-defined structures, making it unstable and vulnerable to changes in staff. One of the main challenges highlighted by the interviewees is the number of problems other than addiction among people in treatment, which makes addiction treatment and recovery difficult to achieve. Nevertheless, the high levels of other problems being treated in Allorfik highlights the need for easily accessible therapy as many find that Allorfik is the only place to turn to in times of crisis. Conclusion Allorfik seems to have been implemented in accordance with original intentions and plans for addiction treatment service but has also become more than just a service for addiction treatment with easy access in a country with vast distances and limited resources.